2017
DOI: 10.1108/scm-06-2016-0197
|View full text |Cite
|
Sign up to set email alerts
|

Analysing supply chain resilience: integrating the constructs in a concept mapping framework via a systematic literature review

Abstract: The purpose of this paper is to analyse the concept of supply chain resilience (SCRES) using a concept mapping framework to seek conceptual clarity, with an emphasis on SCRES definitions, essential capabilities, elements and managerial practices. Design/methodology/approach: A systematic literature review was conducted of 103 peerreviewed journal articles covering the period from 2000 to 2015, with the aim to identify supply chain resilience concept. Findings: Through analysis and synthesis of the literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
711
1
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(808 citation statements)
references
References 117 publications
11
711
1
9
Order By: Relevance
“…This study draws on past reviews and conceptual framework (e.g., Ali et al, ; Hohenstein et al, ) while enriching them and offering unique contributions pertaining to the SCR research areas. More specifically, in addition to integrating and discussing empirical studies, we focus on the whole area at large, to inductively derive meaningful topical areas.…”
Section: Discussion: Findings and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study draws on past reviews and conceptual framework (e.g., Ali et al, ; Hohenstein et al, ) while enriching them and offering unique contributions pertaining to the SCR research areas. More specifically, in addition to integrating and discussing empirical studies, we focus on the whole area at large, to inductively derive meaningful topical areas.…”
Section: Discussion: Findings and Future Directionsmentioning
confidence: 99%
“…Third, we use a robust paper selection process by first using journals and databases in order to find relevant publications and then tracking the references of those articles to find additional meaningful results (Pittaway, Robertson, Munir, Denyer, & Neely, 2004). Finally, in contrast to past reviews focusing on specific aspects of SCR, such as definition and principles (Kamalahmadi & Parast, 2016), antecedents (Ponis & Koronis, 2012), perspectives, concepts and methodologies (Bhamra, Dani, & Burnard, 2011), resilience phases, strategies and capabilities (Ali et al, 2017), this study seeks to inductively identify the key topic areas within SCR (depth), across a wide spectrum of subject areas and approaches (breadth), as well as the gaps and research avenues therein (perspective), in order to provide a broader outlook on the SCR system.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…At the same time, several recent literature reviews on the topic (e.g. Hohenstein et al, 2015;Tukamuhabwa et al, 2015;Kamalahmadi and Parast, 2016;Ali et al, 2017;Kochan and Nowicki, 2018;Stone and Rahimifard, 2018) have shown that SCRes research has established supply chain principles that underpin resilience (Christopher and Peck, 2004;Sheffi, 2005); identified and explored formative elements of resilience (e.g. Jüttner and Maklan, 2011) and their interrelationship (e.g.…”
mentioning
confidence: 99%
“…Although the definitions of resilience vary according to the context (i.e., physical, ecological, socio-ecological, psychological, disaster management, organisational, and engineering), resilience in supply chain (SC) management is defined as 'the ability of a firm to cope with the consequences of unavoidable events in order to return to its original operations or move to a new, more desirable state after being disturbed' [4,5]. SCRES is also primarily represented as the state of the art in which a firm absorbs, adapts to, and restores itself from any disruptive event, ranging from a minor shipment delay to a major earthquake [6]. Further, SCRES has gained attention from both researchers and practitioners, primarily due to two main reasons: (1) The increase in network complexity driven by global transactions and (2) an over-reliance on technology-driven operational solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Hohenstein et al's [13] systematic review of 67 peer-reviewed articles from 2003 to 2013 identified 36 SCRES elements, among which flexibility, redundancy, collaboration, visibility, agility, and multiple sourcing were the top six in terms of the number of appearances in various studies. Recently, Ali et al [6] identified 13 essential resilience elements and 84 managerial practices based on 103 research articles for enhancing firms' capabilities in anticipating, adapting and responding to, and recovering and learning from disruptive events. However, the existing literature has hitherto focused on the comprehensive framework or theory-driven investigation of SCRES.…”
Section: Introductionmentioning
confidence: 99%